Health Equity and Financial Protection in Ghana - World Bank (Washington, DC, 2017)
The health equity and financial protection reports are short country-specific volumes that provide a picture of equity and financial protection in the health sectors of low-and middle-income countries. Topics covered include: inequalities in health outcomes, health behavior and health care utilization; benefit incidence analysis; financial protection; and the progressivity of health care financing. Ghana's government is committed to improving equity and financial protection in the health sector. In 2005, the Government of Ghana amended its growth and poverty reduction strategy report to include a new target in the country's development: to reach middle income status by the year 2015 (Republic of Ghana 2005). Ghana's Minister of health has called attention to the role that health plays in economic development and has placed equity in both access and delivery of health services as a top priority for reaching middle income status (Ministry of health 2007). Ghana spends 8.1 per cent (2009) of its gross domestic product (GDP) on health. This is greater than the spending levels in other lower middle-income countries in Africa, which spend an average of 5.8 per cent (2009) of their GDP on health. Ghana provides free health services for certain vulnerable groups, such as children under five, people over 70, and pregnant women. In addition, immunization and services to combat certain communicable diseases are provided free of charge.